Flying Home: A Mode of Conversion in the African American Context - Hinds, Jay-Paul (Pastoral psychology, 2020)
African American literature has been one of the chief purveyors of African American culture’s folklore tradition. Writers, through fiction and nonfiction accounts, keep alive the stories of such figures as Br’er Rabbit, High John the Conquerer, and John Henry. Other than these manifest folktales, there is also a canon of latent folktales that modern writers are attempting to bring back to African American consciousness. Such is the case with Toni Morrison’s Song of Solomon, a novel that shares the informative and inspirational folktale of flying Africans. This article explores the role that flying plays not only in Morrison’s novel but also its continued relevance and effectiveness for African Americans, and other oppressed communities, seeking liberation. I propose that flying is a mode of religious conversion (i.e., an act of (re-)turning) that has enabled African Americans to come in touch with supernatural resources during times of sociopolitical, communal, and personal sorrow.